HUBUNGAN POWER OTOT LENGAN BAHU DAN POWER OTOT TUNGKAI DENGAN KETEPATAN SMASH BOLA VOLI PADA TIM BOLA VOLI PUTRA SMK NEGERI 2 TELUK KUANTAN - Robi Ramdhani; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is when doing smash the height of jump is very less, so the reach of hand does not exceed top net, which causes the athlete difficult to direct the ball, the opposing player can block the ball and the smash is not sharp, so it does not generate points. The ball is not strong and not fast enough, so the ball can be used again by the opponent to counterattack. From the description of the above problems, it is suspected to be less muscle power shoulder arm and leg muscle power when doing smash volleyball. This study aims to determine whether there is a reletionship of muscle power shoulder arm and leg muscle power with precision smash volleyball on the ball team volley boy SMK Negeri 2 Teluk Kuantan. Sampling technique that is the total population ( total sampling ) atheletes volleyball men SMK Negeri 2 Teluk Kuantan amounted to 12 people. This reseach using correlation techniques. Then, the test data using the normality test, product moment correlation test, and test that Lcalculate variable X1 = 0,1373, Lcalculate variable X2 = 0,1081 and Lcalculate variable Y = 0,1897 where Ltable obtained 0,242 (α = 0,05), with so Lcalculate = 0,1373 < L table 0,242 on variable X1, Lcount 0,1081 < Ltable = 0,242 on the variable X2 and Larithmetic = 0,1897 < Ltable = 0,242 on variable Y, in other words it is concluded that X1, X2 and Y data are distributed normal.Keywords: Power Muscle Shoulder Arm, Leg Muscle Power, Accuracy Smash Volleyball